Trademark activity and the market performance of U.S. commercial banks - González-Pedraz, Carlos; Mayordomo, Sergio (Journal of Business Economics and Management, 2012)
This empirical paper analyzes the effect of trademark activity on the market value and performance of US commercial banks from two perspectives. First, a longterm perspective considers the effect of such activity on banks’ Tobin’s q. Second, with a short-term perspective, the authors analyze the effect of trademark activity on banks’ abnormal returns. An older portfolio of trademarks diminishes the ratio of market value to firm assets, but this ratio can be improved in the long term by abandoning old trade-marks. Portfolios of trademarks with wide diversification do not help increase Tobin’s q. Furthermore, according to an event study, the creation of a trademark has a positive effect on cumulative abnormal returns compared with no event, whereas a cancellation event has a negative impact.